2018
DOI: 10.1016/j.anifeedsci.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Proposal and validation of new indexes to evaluate maize silage fermentative quality in lab-scale ensiling conditions through the use of a receiver operating characteristic analysis

Abstract: In the context of dairy cow feeding, it is increasingly important to know the quality of the maize silage used in the ration and therefore, it appears to be crucial optimizing the techniques necessary to assess it. The aim of this study was to evaluate whether the Flieg-Zimmer's score (FZS), could properly estimate the quality of fermentations of maize silage made in a lab-scale ensiling system, and to calculate and validate new quality indexes suitable for lab-scale fermentations. The experimental dataset was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…In this study, all the hybrids showed an FQI value higher than 48.2, which, according to Andrighetto et al (), represents the cut‐off between excellent and not excellent maize silage from a fermentative point of view, confirming the goodness of the ensiling method used. In this regard, the early hybrids have generally shown a slightly lower production of ammonia, acetic and propionic acid, as also reported by Gerlach et al (), although both compounds have a concentration well below the suggested critical limit (Kung et al, ).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In this study, all the hybrids showed an FQI value higher than 48.2, which, according to Andrighetto et al (), represents the cut‐off between excellent and not excellent maize silage from a fermentative point of view, confirming the goodness of the ensiling method used. In this regard, the early hybrids have generally shown a slightly lower production of ammonia, acetic and propionic acid, as also reported by Gerlach et al (), although both compounds have a concentration well below the suggested critical limit (Kung et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…Each whole maize sample was immediately subjected to determination of DM and WSC content by means of a portable near‐infrared (NIR) system (poliSPEC NIR ; ITPhotonics), using the calibration curve reported in Table . After the analyses, for each of the 522 whole maize samples, two subsamples ( n = 1,044) were immediately ensiled in vacuum‐packed bags (Orved 2633040, Orved SpA), as described by Andrighetto et al ().…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations